Are environmental tax policies beneficial? Learning from programme evaluation studies - Teusch, Jonas (OECD Environment Working Papers, 2019)
This paper provides a concrete example of how policy analysts can use empirical programme evaluation studies to perform ex-post assessments of environmentally related tax policies. A number of studies credibly identify causal effects of environmentally related tax policies, but do not necessarily provide all the information needed to fully inform the policy-making process. This paper argues that cost-benefit analysis (CBA) could enrich ex-post assessments of environmentally related tax policies, given that CBA provides decision makers with a broader perspective of social costs and benefits and allows the identification of potential trade-offs among policy objectives